Novel coronavirus-related acute respiratory distress syndrome in a patient with twin pregnancy: A case report - Harsh Mehta; Sasa Ivanovic; Amanda Cronin; Lindsey VanBrunt; Nirav Mistry; Richard Miller; Paul Yodice; Fariborz Rezai (Elsevier, 2020)
We present the case of a 39-year-old woman, G1P0, who had conceived twins via in-vitro fertilization, who presented at 27 weeks of gestation with nasal congestion and dry cough for 7 days. On presentation, her physical examination was benign, except for sinus tachycardia, and she was oxygenating adequately on room air. Laboratory studies were unremarkable, except a PCR test positive for SARS-COV2, and a CT scan of her chest showed bilateral multi-focal ground-glass opacities. A fetal non-stress test was reassuring. She was treated with intravenous fluids, ceftriaxone, azithromycin, and hydroxychloroquine. During her hospital stay, she developed progressively worsening respiratory failure, initially requiring non-invasive ventilation, and subsequently progressed to acute respiratory distress syndrome requiring mechanical ventilation. She then suffered from sudden hypoxemia and hemodynamic collapse, on maximal ventilatory support, prompting an emergency cesarean section at bedside. This led to rapid stabilization of hemodynamic parameters, and of her overall respiratory status. Both the twins were born prematurely, and one of them tested positive for SARS-COV2.